EXPLAINING MALAYSIA’S MEDIATION IN THE THAILAND-CAMBODIA CONFLICT THROUGH LIBERALISM - Annisa Adlina (Verity: Jurnal Ilmiah Hubungan Internasional (International Relations Journal), 2026)
The border conflict between Thailand and Cambodia escalated again in mid-2025 after a violation of the code of ethics by Prime Minister Paetongtarn Shinawatra, as revealed in a phone recording. Although Shinawatra was ultimately dismissed from his post, the Thai people seemed to rise again to fight for Preah Vihear to be included in their territory. In response, Malaysia, as a neighboring country and the chair of ASEAN 2025, also offered to mediate the Bangkok-Phnom Penh conflict. This paper examines the factors influencing Malaysia's decision through the lens of liberalism. The results of the study indicate that Malaysia is driven to act rationally to guarantee its citizens' rights and create a better life and welfare through international cooperation. Once this is achieved, it is hoped that it can project a new and better state order, referred to as the concept of liberalism as a modern state.